Impactos econômicos do programa Fundopem nas regiões do Rio Grande do Sul : análise usando econometria espacial, 2010-2019 - Busatto, Leonardo Maranhão (2022)
This dissertation consists of an evaluation of the economic impacts generated by the main tax incentive program in the state of Rio Grande do Sul (RS) – Fundopem. Using data from ten years of the program, between 2010 and 2019, the present work sought to analyze the effects of the investments encouraged by the program on the economy of the regions of RS, considering its spatial component. Therefore, an Exploratory Spatial Data Analysis (ESDA) was carried out and, based on the existence of a spatial correlation between the variables, the development of a spatial econometric model using instrumental variables to measure the associated effects between the incentivized investments by the program and the endogenous variables, Industrial Gross Value Added (GVA) and employment rate in industry. Based on the spatial analyses, it was possible to prove that the endogenous variables have spatial autocorrelation and that they have a spatial correlation with the explanatory variables, especially those related to Fundopem. However, the results obtained by the econometric model did not allow to prove that the fulfilment of investments from the program caused economic effects in the municipalities where they were carried out. On the other hand, by including a variable corresponding to a spatially lagged variable of Fundopem program, it was confirmed that doing investments from the program in each municipality affects the industrial GVA of neighboring municipalities, generating an “overflow” effect in the region.